Opportunistic Routing Protocol for Resource Optimization in Vehicular Delay-Tolerant Networks (VDTN) - et. al., S. Parameswari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
VDTNs (Vehicular Delay-Tolerant Networks) are a breakthrough-based DTN solution for vehicular communications in difficult situations of long delays and intermittent connectivity. This technology uses the store-carry-and-forward model to enable in-transit bundles to arrive at their destination asynchronously, hop by hop, over moving vehicles fitted with short-range wireless devices. The VDTN architecture is based on out-of-band signalling with separate control and data planes, and it employs an IP over VDTN strategy. This paper presents an Opportunistic Routing Protocol called OPRNET, which works on the routing decisions based on global location data, and merges a hybrid technique between multiple-copy and single-copy approaches. It also improves the performance by minimized energy consumption in vehicular communication approach. The simulation results from our proposed approach suggest that OPRNET is feasible and can be viewed as a very important technology for vehicular communications, though it does include appropriated technologies for outline interferences and QOS support. OPRNET attempts to optimize network capacity such as storage, latency, and energy consumption while increasing distribution chance and reducing latency and overhead.